impact of derivative hedging on risk: evidence from China - PAN, YIFAN (2022)
The use of derivatives by companies is now increasing and there is a lot of research on the use of derivatives to hedge risk by European and American companies, but relatively little research on Asian companies. This paper selects company data for 2020 and 2021 from 327 companies listed on the Hong Kong Stock Exchange, collects information on the use of derivatives by reading the companies' annual reports, and performs regression analysis in conjunction with the companies' risk and other data. The study finds that the use of derivatives can both reduce and increase company risk. Through further sub-group studies, it was found that the use of derivative hedging was more effective in reducing risk when the company's risk was higher and that the effect of hedging risk became less pronounced when the statistical time lengthened. The findings of this paper are based on a study of Asian companies. A new research perspective is provided to study the impact of derivatives on corporate risk.